"How Do We Stop Trying to Do It All?" Application of the Family Business Parallel Planning Process. (January 2021) - Davidson, Amber; Berka, Gregory; Meador, Cami
Keith Lang, a then college senior, and his mother, Lori, launched Global Logistics & Shipping Partners (GLS) overnight when an opportunity presented itself to secure a number of clients. From Week 1, they were focused on exceptional client support and service without any infrastructure in place. Holly Primrose, Keith's long-time girlfriend, who still had a year left in college, jumped in to help. Now 15 years later, the business grew to 22 employees, while experiencing many revenue challenges. Keith and Holly worked tirelessly for 15 years straight with an equal focus on clients, ethics, and GLS's employees. After having a family and investing in other endeavors, Keith and Holly found themselves in a position where they needed to make decisions regarding the future vision for GLS and themselves. They desired to remain engaged with GLS but also to spend as much time as possible with family and personal interests. The case provides information that allows students to apply Carlock and Ward's family business parellel planning process to evaluate a family business' goals, evaluate the owners' personal goals, and find synergies across professional and personal goals and visions.